Understanding women's claim to land in an Eastern Cape Village - Luwaya, Nolundi (Department of Public Law, 2019)
The history of land dispossession in South Africa affected communities in the former homelands in multiple ways. The laws used to implement policies of segregation and dispossession undermined the rights to land held by black South Africans living in the countryside. Women living in these communities suffered under the dual burden of diminished status in the eyes of the law and landlessness. This history has shaped the current reality of women living on communal land in rural South Africa and has influenced the development and security of their land rights. In the context of a Constitutionally protected right to secure tenure, this dissertation discusses relevant literature, past legislative interventions and present-day laws, bills and policies in order to foreground the powerful role of framing in determining whose land rights are recognised and protected. Drawing on further literature and empirical research I discuss the interaction between top down approaches to framing laws and the assignment of status, an aspect that is crucial for black women. I discuss this alongside the lived experiences of women claiming residential land in a rural Eastern Cape community in order to foreground the inherent shortcomings of such top down approaches and their inability to fully recognise and protect the land rights of rural women.